Determinants affecting consumer ethnocentrism towards Malaysian consumer at PIJ Holdings Sdn Bhd - Johar Amin, Nurul Ili (2017)
Consumer ethnocentrism is a belief or a views held by a consumer on specifically on their purchasing behaviour. Consumer that shows a high ethnocentric tendencies usually views that it is wrong and even immoral for local people to buy product from another country. There are many factor that affect consumer ethnocentrism. Varies from demographic, sociosychological, economic and even politic, but the study however only test on one factor which is socio-psychological factor. These socio-psychological factors are cultural openness, patriotism, cosmopolitanism and nationalism. Therefore, the specific objective of this study is to find the relationship between these socio-psychological factor on consumer ethnocentrism towards Malaysian consumer specifically at PIJ Holdings Sdn Bhd. The sample size of the study comprises of 50 resondents from PIJ Holdings Sdn Bhd. An online survey was was used to collect data on respondent’s demographic profile, socio-psychological antecedent tendencies and consumer ethnocentric tendencies. The result of the findings revealed that two socio-psychological factor, Patriotism and Nationalism has a medium positive linear relationship and significant with consumer ethnocentrism while the other two variables, cosmopolitanism and cultural openness show an also medium positive linear relationship but not significant.